Exploring the motivations and needs of primary stakeholders in promoting economic responsibility for women’s sport: A Stakeholder theory perspective on the National League - Farahani, Atiye (2025)
Despite Finland’s progress in gender equality, women’s football continues to encounter economic and structural challenges. This master’s thesis explores how the Finnish Women’s National League can strengthen economic responsibility by identifying and addressing the needs and motivations of its key stakeholders—players, coaches, managers, and a sponsor—through the lens of stakeholder theory. A qualitative research design was applied, using ten semi-structured interviews and thematic analysis to uncover stakeholder experiences and perceptions related to economic responsibility. Findings reveal that longstanding structural constraints limit stakeholder contributions. Players emphasize passion and ambition yet face economic insecurity, under-funded foundations, and limited visibility. Coaches report inadequate facilities, piecemeal funding, and the need for fair recognition. Managers describe fragile income structures, resource shortages, and difficulties boosting fan engagement while striving for competitive fairness. The sponsor highlights a “visibility–payoff paradox,” aspiring toward full professionalization and motivated by both brand impact and social equity. Cross-group synthesis underscores a shared demand for transparent governance, sustainable funding mechanisms, and enhanced professionalization, along with targeted marketing (e.g., femvertising) and capacity-building programmes to improve resource allocation and stakeholder collaboration. Based on the results, the following measures are recommended to improve transparent governance and ensure long-term viability and gender equity: establishing a professionalization fund, promoting femvertising, enhancing capacity-building, prioritizing player welfare, and adopting hybrid ROI–equity sponsorship models to better align stakeholders.